PHYSICAL SELF-PERCEPTIONS AND SELF-ESTEEM IN RELATION TO BODY MASS STATUS AMONG FEMALE ADOLESCENTS - Petra Dolenc (Innovative Issues and Approaches in Social Sciences, 2016)
The purpose of the study was to examine the physical self-concept and self-esteem in adolescent girls aged between 13 and 18 years in relation to their body mass status. The Slovenian version of the Self-Description Questionnaire (PSDQ) was used to determine the multidimensional physical self-concept among participants. The results indicated that overweight girls reported greater body dissatisfaction in terms self-perceived body fat and physical appearance compared to normal-weight girls. Overweight girls also achieved significantly lower scores in the self-perceived physical abilities, as well as global physical-self and self-esteem than normal-weight peers. As expected, underweight girls reported the lowest amount of body fat. Moreover, they reported lower levels of physical activity than normal-weight peers and had less physical strength compared to the other body mass index categories. The findings has significant implications for the work with adolescent girls in terms of developing appropriate educational intervention and physical education programmes aimed towards reinforcing and increasing self-esteem and promoting active lifestyle.